Proximate, Mineral and Antinutrient Compositions of Natural Cocoa Cake, Cocoa Liquor and Alkalized Cocoa Powders Sourced in Nigeria - Ilesanmi Adeyeye, Emmanuel (Journal of Advanced Pharmaceutical Science And Technology, 2016)
An investigation into the proximate, mineral and antinutitional constitutents of natural cocoa powder (NCP), natural cocoa liquor (NCL) and alkalized cocoa powder (ACP) was carried out. Other parameters investigated were: energy values as contributed to the total metabolisable energy by protein, fat and carbohydrate and the energy percentages; calculated mineral quality parameters; mineral bioavailability as predicted by Ca: Phy, Phy:Zn and CaPhy/Zn molar ratios of the different cocoa products and mineral safety index (MSI) of some of the minerals of the samples. The data generated were subjected to statistical evaluation of chi-square (χ2). The three samples, NCP, NCL and ACP had proximate levels (g/100g) as: total ash, 3.73-10.8; moisture, 2.16-9.04; protein, 10.9-24.3; fat, 4.93-56.0; fibre, 1.03-17.3; carbohydrate, 20.5-48.9 and fatty acid, 3.95-44.8. For total energy contribution, results varied from, 1169-2656 kJ/100 g. In the minerals, the followings were higlhly concentrated: Na, K, Ca, Mg, Zn, Fe and P but low or not detected in Cu, Co and Mn. Virtually all the mineral quality parameters were poor as seen in these ratios: K/Na, Na/K, Ca/P and K/(Ca + Mg). The molar ratios of the samples were good enough to predict the bioavailability of the minerals. The mineral safety index (MSI) values showed that no mineral reached the toxic level in any of the samples. In the antinutritional constituents, ACP was highest in phytin phosphorus (Pp), phytin and Pp % of P; NCL was highest in oxalate and total phosphorus (P); tannin was highest in NCP. χ2 was significant in all proximate values (except ash, moisture and organic matter); all energy contributions, significant only in Mn (among the minerals); non was significant in the mineral quality parameters; only Ca: Phy was significant in the mineral molar ratios; no value was significant in the MSI and phytin was the only parameter significant among the antinutritional constituents.
Keywords: Proximate; mineral; antinutrient; compositions; cocoa processed products